2
\begin{equation*} 
\begin{aligned}
E(X) & = \sum_{x=0}^{\infty}x\frac{e^{ - \lambda }\lambda ^x}{x!} \\
     & = \sum_{x=0}^{\infty} \frac{e^{ - \lambda }\lambda ^x }{(x-1)!} \\
     & = \sum_{x=1}^{\infty}\frac{e^{ - \lambda } \lambda ^x }{(x-1)!} \\
     & = \lambda \sum_{x=1}^{\infty} \frac{e^{ - \lambda } \lambda ^{(x-1)} }{(x-1)!} \\
    \shortintertext{Now, let us substitute x-1 by y, then}
E(X) & = \lambda \sum_{y=0}^{\infty} \frac{e^{ - \lambda } \lambda^y }{y!} \\
     & = \lambda
\end{aligned}
\end{equation*}

enter image description here

My code and the result displayed are as above, how can I move that intertext to the left? Also, how can I reduce the space before the aligned part? I'm using packages amsmath and mathtools.

3

You write your equation an quite complicated way. Tray:

\documentclass{article}
    \usepackage{mathtools}

\usepackage[active,displaymath,tightpage]{preview}% for show only tcolorbox
    \setlength\PreviewBorder{1em}

    \begin{document}
\begin{align*}
E(X) & = \sum_{x=0}^{\infty}x\frac{e^{ - \lambda }\lambda ^x}{x!} \\
     & = \sum_{x=0}^{\infty} \frac{e^{ - \lambda }\lambda ^x }{(x-1)!} \\
     & = \sum_{x=1}^{\infty}\frac{e^{ - \lambda } \lambda ^x }{(x-1)!} \\
     & = \lambda \sum_{x=1}^{\infty} \frac{e^{ - \lambda } \lambda ^{(x-1)} }{(x-1)!} 
    \shortintertext{Now, let us substitute $x-1$ by $y$, then}
E(X) & = \lambda \sum_{y=0}^{\infty} \frac{e^{ - \lambda } \lambda^y }{y!} \\
     & = \lambda
\end{align*}
    \end{document}

which gives:

enter image description here

The cause of your problem seems to be equation* environment which doesn't allow to use \intertext or shortintertext in it.

  • @AudreyFeng, glad to hear this! Than you can accept answer (by tick on the check mark at the top left of answer ...) :-) – Zarko Jan 22 '16 at 4:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.